2018
DOI: 10.1007/s11274-018-2531-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Bacillus subtilis as a robust workhorse for production of heterologous proteins and beyond

Abstract: Bacillus subtilis, belonging to the type species of Bacillus, is a type of soil-derived, low %G+C, endospore-forming Gram-positive bacterium. After the discovery of B. subtilis 168 that displayed natural competence, this bacterium has been intensively considered to be an ideal model organism and a robust host to study several basic mechanisms, such as metabolism, gene regulation, bacterial differentiation, and application for industrial purposes, such as heterologous protein expression and the overproduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 162 publications
0
89
0
2
Order By: Relevance
“…3). Promoters are important cis-regulatory elements for regulating gene expression and would impact on protein production (Cui et al 2018). However, previous reports showed that enhancing the strength of the promoter increased enzyme production at different levels, from 7.62 to 79.9% of increase under different dual-promoter strategies (Liu et al 2019;Okegawa and Motohashi 2016).…”
Section: Discussionmentioning
confidence: 99%
“…3). Promoters are important cis-regulatory elements for regulating gene expression and would impact on protein production (Cui et al 2018). However, previous reports showed that enhancing the strength of the promoter increased enzyme production at different levels, from 7.62 to 79.9% of increase under different dual-promoter strategies (Liu et al 2019;Okegawa and Motohashi 2016).…”
Section: Discussionmentioning
confidence: 99%
“…; Cui et al . ). This review aims to detail the latest developments of hosts for protein expression in Bacillus , including secretion pathway optimization, mRNA and protein stability enhancement, cell growth facilitation, genome streamlining and engineering transcriptional regulators (Table and Fig.…”
Section: Introductionmentioning
confidence: 97%
“…have been produced by bacteria and fungi, including Escherichia coli, Bacillus, Pichia pastoris, Trichoderma reesei, Aspergillus niger, etc. Compared to other expression systems, Bacillus species are regarded as the promising host strains with various merits, including nontoxicity, convenience for gene modification, short fermentation cycle on cheap nutrition, superior capacity of protein secretion and robustness in industrial fermentation (van Dijl and Hecker 2013;Cui et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant negative metabolic phenomenon occurring in batch mode is carbon catabolite repression. As organisms quickly have to react to changing nutritional conditions, promoters of genes related to catabolism are considered to be strong and are thus frequently used for recombinant protein production (Cui et al, ; Hubmann, Thevelein, & Nevoigt, ; Kluge, Terfehr, & Kück, ; Stöckmann et al, ). However, the induction or repression of these promoters is directly coupled with the availability of the preferred carbon source, which most often is glucose.…”
Section: Introductionmentioning
confidence: 99%